2008
DOI: 10.1590/s1516-35982008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Substituição total do milho por sorgo e óleo de abatedouro avícola em dietas para frangos de corte

Abstract: RESUMO -Com o objetivo de avaliar o efeito da substituição total do milho por sorgo e níveis crescentes de óleo de abatedouro avícola (OAA) sobre os parâmetros de desempenho, as características e o rendimento de carcaça de frangos de corte, foram utilizados 260 pintos de 1 dia, machos, da linhagem Cobb, submetidos aos seguintes tratamentos: uma ração-referência à base de milho e quatro rações à base de sorgo com inclusões de 0; 2,5; 5 e 7,5% de OAA de acordo com as fases de criação(1 a 7 dias, 8 a 21 dias, 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
2
5
1
11
Order By: Relevance
“…The obtained results indicate that similarly to what has been reported for fast-growth broilers (Garcia et al, 2005;Rocha et al, 2008), sorghum can be used as a total substitute to corn in the feeding of slow-growth broilers without impairing the animal performance. It is known that the metabolizable energy has been reported to be the main dietary factor affecting voluntary feed intake by birds (Freitas et al, 2011); thus, it can be inferred that the absence of a significant effect of inclusion of ASB on FI and consequently on WG and FC may be associated with the good evaluation of the feed's metabolizable energy, since diets were calculated to be isoenergetic, considering the metabolizable energy values of ASB determined for slow-growth broilers at different ages.…”
Section: Resultssupporting
confidence: 83%
“…The obtained results indicate that similarly to what has been reported for fast-growth broilers (Garcia et al, 2005;Rocha et al, 2008), sorghum can be used as a total substitute to corn in the feeding of slow-growth broilers without impairing the animal performance. It is known that the metabolizable energy has been reported to be the main dietary factor affecting voluntary feed intake by birds (Freitas et al, 2011); thus, it can be inferred that the absence of a significant effect of inclusion of ASB on FI and consequently on WG and FC may be associated with the good evaluation of the feed's metabolizable energy, since diets were calculated to be isoenergetic, considering the metabolizable energy values of ASB determined for slow-growth broilers at different ages.…”
Section: Resultssupporting
confidence: 83%
“…In another study, the addition of up to 7.5% poultry slaughterhouse oil in sorghum-based diets did not affect the carcass yields of broilers (ROCHA et al, 2008). ANDREOTTI et al (2004) made the same observation in a diet with up to 7.86% soybean oil at 21 to 42 days.…”
Section: ------------------------------------------------------------mentioning
confidence: 72%
“…Garcia et al (2005) evaluated the performance and meat quality of broilers, and found no negative effect of corn replacing for sorghum, as well as Morais et al (2002), Pimentel et al (2007) and Rocha et al (2008), who observed that the use of sorghum as an alternative to corn proved advantageous in broilers diets.…”
Section: Effects Of Sorghum On Broilers Gastrointestinal Tractmentioning
confidence: 99%